(3cJGH GdeHOC hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3YHO Gddg Hf eMeO Hf YeQ GdNWjH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEfi CQOj Cf COd ai gPg GdebGdI Ydi MbjbI eG YfO GdeTGFjf GdeMUdjf ef MGd GdeHOC hGdejYGO s
(3BNQgG (B:s
(3agPG ZGjI eG CQOfG Cf fhOYg dcJGHfG gPG Je cJGH GdeHOC hGdejYGO s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B891 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1456s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs